19th Annual U.C. Berkeley Heavy at Claremont Hotel-Berkeley - Watkins, Howard::::::::: (1987)
On floor: Teresa Pricco, Alan Pricco, David Morse, Kathy Muniz, David Atkinson, Lori Beresford, Bill Walker (no tie), John Beresford, Cynthia Nicholson and Greg Nicholson; seated: Dale Mesple, Terri Mesple, Denise Morse, Jerry Neary, Bonnie Neary, Cathy Barkett, Joe Barkett, George Garofalo, Heidi Pieczonka Garofalo (in green dress), Frank Gumpert, Janie Gumpert, Christine Watkins and Howard Watkins standing